A cationic porous polymer as a robust and recyclable adsorbent for the removal of harmful dyes from aqueous contaminants. Issue 10 (15th September 2022) - Chandra, Bijan Krishna; Majee, Adinath; Bhaumik, Asim
Abstract : A new cationic porous organic polymer (VBT-POP) has been synthesized and it showed excellent selective and quantitative adsorptive removal of anionic dyes RB (1252 mg g −1 ) and XO (735 mg g −1 ). Abstract : Adsorptive removal of organic dyes is considered as one of the most advanced technologies for water purification. Herein, a new nitrogen rich cationic porous organic polymer (VBT-POP) has been synthesized through the aqueous phase radical polymerization of triallylamine and ( p -vinylbenzyl)trimethylammonium chloride. VBT-POP has been thoroughly characterized and used for the selective and quantitative adsorptive removal of two anionic dyes rose bengal (RB) and xylenol orange (XO) under different conditions. The VBT-POP is chemically and thermally robust in nature with a positive zeta potential. VBT-POP follows pseudo-second order adsorption kinetics for these two dyes. It follows the Langmuir adsorption isotherm with exceptionally high dye uptake capacities of 1252 mg g −1 for RB and 735 mg g −1 for XO. Sorption properties are compared considering the effects of pH and temperature. Calculation of various thermodynamic parameters reveals endothermic spontaneous adsorption along with wide pH range applicability. A proposed electrostatic interaction model of the adsorption mechanism has also been explored. Alkaline NaCl solutions almost completely desorb the adsorbed dyes through ultrasound treatment (UT). VBT-POP exhibited very good recyclability and high stability for the removal of these dyes from contaminated aqueous solutions for several consecutive adsorption cycles.